Traumatic corneal perforation with exteriorisation of Ahmed glaucoma valve tube - Kumar, Suresh (BMJ Case Rep, 2018)
We report a rare case of traumatic corneal perforation with Ahmed glaucoma valve (AGV) tube. A 5-year-old female child, diagnosed with refractory glaucoma, had undergone AGV implantation, presented with the posterior migration of AGV tube after trauma to the eye. The detailed ocular history, ophthalmic findings, clinical course and surgical management are discussed.